Artificial Beings in Archaeology: Bridging Historical Reality and Digital Simulation - Bertoldi, Stefano; Valenti, Marco (Archeomatica, 2024)
The "Johannes" project represents an innovative intersection of archaeology and artificial intelligence, aiming to reconstruct and simulate the consciousness of a medieval individual based on extensive archaeological data. By utilizing AI, specifically a ChatGPT model, the project seeks to bridge the gap between material culture and digital self-awareness. The AI is populated with data from the archaeological site of Miranduolo, integrating information about the village's historical context, material culture, and societal structures from the 7th to the early 14th century. This project explores the challenges of limiting the AI's knowledge to what would have been known by a 12th-century individual, thereby enriching the AI's "memories" with sensory experiences and historically plausible narratives. The project raises significant questions about the potential of AI in historical reconstruction, particularly in the simulation of emotions, empathy, and self-awareness. Ultimately, "Johannes" is not merely an intelligent collection of data but an experimental artificial being capable of critical thought, subjective experiences, and emotional expression. The implications of this project extend beyond archaeology, offering new perspectives on the use of AI in understanding the past and its potential as a teaching tool and a medium for theoretical exploration.